A modified system analysis code for thermo-hydraulic calculation of hydrogen in a nuclear thermal propulsion (NTP) system. (15th December 2021) - Han, Zichao; Zhang, Jing; Wang, Mingjun; Tian, Wenxi; Qiu, Suizheng; Su, G.H.
Highlights: The system analysis code RELAP5 is modified for calculation of NTP systems. The physical property models of hydrogen are implemented into the code. The correlations of heat transfer coefficient and friction factor are implemented into the code. The heat conduction between the inner and outer cores should be considered when simulate a two-pass NTP reactor core. Abstract: Taking advantages of long lifetime and high power density, nuclear thermal propulsion (NTP) has become an advanced propulsion option in some special power fields. Due to the high heat release and dramatic density change, the flow instability and subsequent unbalance of flow and heat transfer would happen. The thermo-hydraulic calculation of working medium is an important part of the NTP system designing work, and the system analysis methods should be developed. In this study, the system analysis code RELAP5 was modified with the thermo-physical properties, flow and heat transfer correlations of the propellant hydrogen. The modified system code has been validated against the published experiment data. The calculation results show good agreement with the experimental results and the code ELM's calculation results. The modified code was applied to thermo-hydraulic calculation of hydrogen in the analysis of a typical NTP system. The results indicate that the heat conduction between the inner and outer cores should be considered in the calculation of a two-pass NTP reactor core. This study has provided a reference for developing an NTP system analysis code.